2014
DOI: 10.1128/aem.04260-13
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Human Norovirus in Contaminated Oysters and Clams by High Hydrostatic Pressure

Abstract: cHuman norovirus (NoV) is the most frequent causative agent of food-borne disease associated with shellfish consumption. In this study, the effect of high hydrostatic pressure (HHP) on inactivation of NoV was determined. Genogroup I.1 (GI.1) or genogroup II.4 (GII.4) NoV was inoculated into oyster homogenates and treated at 300 to 600 MPa at 25, 6, and 1°C for 5 min. After HHP, samples were treated with RNase and viral particles were extracted with porcine gastric mucin (PGM)-conjugated magnetic beads (PGM-MBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…Since the mechanism of viral inactivation by high pressure is the perturbation of the viral capsid and receptorbinding ability, intact viral particles, but not damaged particles, should be able to bind to PGM-MBs. Using this method, Ye et al (27) found that 600 MPa for 5 min at 6°C was required for reduction below the detection limit (Ͼ4.1-log reduction) of the HuNoV GI.1 strain, which seems to be consistent with a recent human volunteer study. Leon et al (22) reported that HPP at 600 MPa and 6°C for 5 min, but not 5-min 400-MPa treatments (at 6°C or 25°C), completely inactivated 4 logs of the GI.1 HuNoV within seeded oysters.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Since the mechanism of viral inactivation by high pressure is the perturbation of the viral capsid and receptorbinding ability, intact viral particles, but not damaged particles, should be able to bind to PGM-MBs. Using this method, Ye et al (27) found that 600 MPa for 5 min at 6°C was required for reduction below the detection limit (Ͼ4.1-log reduction) of the HuNoV GI.1 strain, which seems to be consistent with a recent human volunteer study. Leon et al (22) reported that HPP at 600 MPa and 6°C for 5 min, but not 5-min 400-MPa treatments (at 6°C or 25°C), completely inactivated 4 logs of the GI.1 HuNoV within seeded oysters.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, hepatitis A virus (HAV), another picornavirus, was found to be more sensitive to HPP, especially under acidic conditions, with more than a 5-log virus reduction observed after treatment at 400 MPa for 1 min (31). Recently, Li et al (26) and Ye et al (27) found that HuNoV strains from two different genogroups (G1.1 and GII.4) showed different sensitivity to HPP using a PGM-MB binding assay. Specifically, a 3.6-log reduction of GII.4 was observed in oyster homogenate at 400 MPa and 6°C for 5 min, whereas only 1.3 logs of GI.1 lost binding ability under the same conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inactivation of surrogates in other foods, such as milk, juice, strawberry puree, and blueberries, will expand the application of HHP pathogen inactivation to a variety of foods (47,48,62). A recent study on the use of HHP on contaminated oysters and clams found that 300 MPa did not inactivate GI and GII noroviruses (63). Several studies on the use of HHP to inactivate surrogate viruses seeded in a variety of nonfood matrices have been published (47,62,(64)(65)(66)(67)(68).…”
Section: Fig 7 Reductions In Tuv Infectivity and In Tuv And Human Normentioning
confidence: 99%